Motivation and Forms of Student Activities in Religious Organizations - Muhammad Zalnur; Zilham Usral; Rustiya Rustiya; Rizal Safarudin (International Journal of Multidisciplinary Research of Higher Education, 2022)
Religious organizations are a place and means for students to develop their abilities. This research aims to find out what the real motivations of students are to join religious organizations and what are the forms of student activity in religious organizations. This research uses a qualitative method with a case study approach. Data sources were taken from 12 informants through in-depth interviews who were selected using techniques purposive sampling, all informants are students who are still active in religious organizations at Padang State University. All interview results were then analyzed thematically using the Analysis Interactive Model Milles & Hubberman analysis models. Overall the results of the analysis show that there are four motivations and six forms of student activity in religious organizations. The four motivations are i) wanting to deepen religious knowledge, ii) expanding relationships, iii) adding organizational experience, iv) according to the major in college. There are six forms of student activities in religious organizations, namely i) participating in Islamic studies/tabligh akbar/Islamic webinars, ii) discussing religious issues iii) raising funds for social assistance, iv) orphanage visits, v) becoming a committee/administrator of a religious organization, vi) training organizational basis. The results of this study can be used as initial data for further researchers in studying this problem in different contexts and issues.